Вплив постійного електричного поля на структуру та властивості полімерів та їхніх композитів - Унрод, В.І.; Демченко, В.Л. (Вісник Українського матеріалознавчого товариства, 2013)
Review is devoted to the analysis of the literature on the effects of constant electric field on the structure and properties of polymers and their composites. Shown that polymeric materials obtained in an electric field, characterized by a more ordered structure and improve the thermal, dielectric, thermo-mechanical and physical properties.